Currency Moderates Quality Experience Influenced by Co-Creation and Excellent Service at Sinar Jaya Bus Transportation Services - Bintarti, Surya; Krisanti, Sheila Ramadhani (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Transportation is a major need in the community's economy. The role of transportation has a very positive impact on regional economic development as a whole, especially in relations between organizations. Realizing the importance of transportation, several parties have decided to open transportation service companies that aim to help the community and make transportation a business sector. The quality of customer experience has become an important concept in consumer behavior research. The conceptualization of experience quality includes visitors' affective responses to the psychological benefits they want from their visiting experience. This growth is influenced by several 7p factors, namely promotion, physical, place, people, and price. This research shows the influence or role of other variables outside of product variation and service quality on the quality of experience, namely price. This research aims to test and explain whether Co-Creation and Excellent Service offered by Sinar Jaya bus transportation services have an effect on Quality Experience with Currency as Moderation. The sampling method in this research used Non-Probability Sampling which is purposive sampling, resulting in the acquisition of data from 103 respondents who had used the Sinar Jaya Bus Transportation Service and then a feasibility test was carried out using the help of the SmartPLS 3.2.9 Program through a validity test, discriminant validity test, and reliability test. The results of data feasibility testing obtained convergence validity, discriminant validity, and reliability values ​​> 0.7 so that this research could be declared valid.